Dynamic Phosphonic Bridges in Aqueous Uranyl Clusters. Issue 6 (1st February 2016) - Oliveri, Anna F.; Pilgrim, Corey D.; Qiu, Jie; Colla, Christopher A.; Burns, Peter C.; Casey, William H.
Abstract: The uranyl cage clusters (UO2 )22 (O2 )15 (PHO3 )20 (H2 O)10 26– (U22 ) and (UO2 )28 (O2 )20 (PHO3 )24 (H2 O)12 32– (U28 ) can be probed in aqueous solutions by using a combination of 1 H Diffusion‐Ordered Spectroscopy (DOSY) and 1 H‐ 31 P Heteronuclear‐Single Quantum Coherence (HSQC) spectroscopy. This class of clusters is ideal for 1 H NMR analysis in D2 O because of the covalent character of the H–P bond in the phosphonic bridges. 1 H DOSY indicates that the clusters are stable in solution and provides hydrodynamic radii of 9.8 ± 0.4 Å for theU22 and 12.3 ± 0.5 Å for theU28 clusters. Furthermore, 1 H‐ 31 P HSQC delivers unequivocal signal assignment for both nuclei, which enables solution dynamics to be monitored by variable‐temperature experiments, and reveals the presence of phosphonic‐bridge conformers. The results provide some of the first dynamic information about steady conformational changes in these enormous actinide macroions. Abstract : The phosphonic bridges in the uranyl cage clustersU22 andU28 have been monitored in aqueous solutions using the unique combination of 1 H DOSY and 1 H‐ 31 P HSQC spectroscopy. The hydrodynamic radii of these clusters are measured to be 9.8 ± 0.4 Å (U22 ) and 12.3 ± 0.5 Å for the (U28 ) in D2 O. Relating specific sites in the structures of these clusters to NMR signals reveals the presence of phosphonic‐bridge conformers.